Pengaruh Tinggi Unggun pada Proses Adsorpsi Ion Besi (Fe2+) Menggunakan Adsorben Arang Aktif Batang Bambu Teraktivasi NaOH - Cory Dian Al'farisi; Rozzana Sri Irianty; Nurfatihayati Nurfatihayati; Suhendri Suhendri; Ariya Eka Alel; Rizky Al Rasyid; Samuel Valentino L Tobing (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2026)
Escalating discharges from metallurgical, textile, and mining industries have led to elevated concentrations of iron (Fe) in aquatic environments, where its persistence and redox activity pose significant risks to water quality and aquatic ecosystems, thereby necessitating the development of efficient and environmentally benign wastewater treatment strategies specifically targeting Fe removal. This study aims to determine the effect of bed height and flow rate on the adsorption capacity and removal efficiency process of iron (Fe²⁺) ions using activated carbon adsorbent derived from bamboo stems and activated with a 0.5 N NaOH solution. Adsorption was conducted in a continuous column system with variations in bed height (15 cm, 20 cm, and 25 cm) and flow rate (2 ml/s, 4 ml/s, and 6 ml/s). The activated carbon was characterized based on the Indonesian National Standard (SNI 06-3730-1995) to maintain product quality, including moisture content, ash content, and iodine number tests. The characterization results indicate that the activated carbon met quality standards, with 7% moisture content, 9% ash content, and an iodine number of 983.475 mg/g. The concentration of iron ions was analyzed using a UV-Vis spectrophotometer. The results indicate that the optimal adsorption capacity was obtained at a bed height of 15 cm and a flow rate of 2 mL/s, with a value of 1.114 mg/g, while the highest adsorption efficiency of 93.8% was achieved at a bed height of 25 cm and a flow rate of 2 mL/s.